Effectiveness of strength training in managing patellofemoral pain syndrome - Salem Alaffari, Naif; Shihab, Rabie Abdulhakim; Alshehri, Mohammed Abdullah; Altalidi, Safiyah Saeed; Kamal, Ibtihal Atef; Alshahrani, Aisha Abdullah; Alshehri, Bodour Ali; Almassaud, Hisham Ahmed; Asiri, Ahmed Ibrahim (International Journal Of Community Medicine And Public Health, 2024)
Patellofemoral pain syndrome (PFPS) is a prevalent musculoskeletal condition, often affecting active individuals and linked to biomechanical imbalances, muscle weakness, and poor neuromuscular control. Among various treatment strategies, strength training has emerged as a cornerstone approach for managing pain and improving function. Strengthening exercises targeting the quadriceps, hip abductors, and external rotators directly address the muscle imbalances responsible for patellar maltracking and joint stress. Evidence demonstrates that progressive resistance training not only alleviates symptoms but also enhances neuromuscular coordination and functional stability, particularly during dynamic activities. Comparisons between strength training and alternative therapies such as manual therapy, taping, and electrical stimulation reveal the superior long-term benefits of active interventions. While passive approaches offer temporary relief, strength training achieves sustained improvements by targeting the underlying causes of PFPS. Moreover, integrating strength exercises into regular physical activity routines amplifies the therapeutic effects and promotes overall musculoskeletal health. The long-term sustainability of strength training outcomes is influenced by adherence, patient education, and the inclusion of progressive overload in exercise regimens. Studies indicate that patients who maintain consistent training routines experience fewer recurrences of symptoms and better quality of life. Combining strength training with aerobic activities further enhances overall physical and psychological well-being. The mechanisms by which strength training exerts its benefits include improved muscle strength, joint alignment, and reduced patellofemoral joint stress. These adaptations result in enhanced functional capacity and pain relief, supporting the role of strength training as a durable and effective intervention for PFPS. Through its multifaceted impact, strength training remains a vital component in the conservative management of PFPS, offering long-lasting relief and functional recovery for affected individuals.